Needs Analysis of the CG2G Digital Module for ICT and Environmental Literacy - Kamaruzaman, Nor Khairunnisa Husna Binti; Osman, Kamisah; Arsad, Nurazidawati Mohamad (PT Mattawang Mediatama Solution, 2025)
The integration of ICT literacy and environmental education plays a vital role in fostering sustainable learning. Nevertheless, rural students continue to encounter barriers such as limited digital competence, unequal access to technology, and insufficient educational resources. This study examined the learning needs for developing the CG2G Digital Module, which integrates ICT and environmental literacy within the ASSURE instructional design framework. A quantitative survey was administered to 47 Year Six students from a rural primary school in Hulu Terengganu, Malaysia. Data obtained through a validated questionnaire based on the VAK Learning Styles Self-Assessment were analyzed descriptively to identify learners’ characteristics, competencies, and preferences. The findings indicated moderate ICT proficiency, particularly in basic computer and internet use, alongside strong environmental awareness in areas such as recycling and water conservation. The dominance of kinesthetic learning preferences suggests the need for multimodal and interactive instructional strategies. These insights provide a foundation for designing the CG2G module to enhance ICT and environmental literacy among rural learners.